The ECB’s New Monetary Policy Strategy - Peter Hennecke (Intereconomics)
Abstract The ECB updated its monetary policy strategy for the first time in 18 years in July 2021. Therein, the ECB announced that it is willing to accept a transitory period of moderate inflation overshoot in its efforts to push inflation upwards after a long period of undershooting its target. This study explores whether such an overshoot can be economically justified employing a simple Phillips curve model. The results point to the conclusion that the average inflation rate over the business cycle consolidated about one percentage point below the ECB’s target rate. A temporary asymmetry of the ECB’s monetary strategy seems therefore justified to realign inflation and inflation expectations with the target rate.